3D gold dendrite and reduced graphene oxide-chitosan nanocomposite-based immunosensor for carcinoembryonic antigen detection in clinical settings - Purohit B.; Kumar A.; Kumari R.; Mahato K.; Roy S.; Srivastava A.; Chandra P. (My University, 2025)
Electrodeposited metallic nanostructures with tree-like hierarchical morphology, often termed metallic nanodendrites (MNDs), are gradually gaining interest in the development of electrochemical biosensors. Noble metal nanodendrites exhibit exceptional conductive and electrocatalytic activity. In this work, we have reported a robust method of electrodeposition of gold nanodendrites (AuND). In order to achieve this, we first optimized the number of gold nanoparticles (AuNP) as seed molecules on the sensor surface and observed that “less seed” resulted in enhanced growth of AuND. Thereafter, AuNP/AuND was used as an excellent surface in conjugation with reduced graphene oxide (rGO), chitosan (CS), and an Anti-CEA antibody for electrochemical detection of carcinoembryonic antigen (CEA), a clinically established cancer biomarker. The developed immunosensor, glassy carbon electrode/gold nanoparticle/gold nanodendrites/chitosan-reduced graphene oxide/Anti-CEA antibody (GCE/AuNP/AuND/CS-rGO/Anti-CEA), is capable of detecting the biomarker in the linear dynamic range (LDR) of 1 × 10−13 to 1 × 10−8 g/mL, which covers the normal as well as clinical range of CEA in serum with a limit of detection (LOD) of 2.23 (±0.03) x 10−14 g/mL. Real sample analysis was performed in serum with a recovery rate ranging between 90 and 99.20 %, demonstrating the feasibility of the sensors for CEA monitoring. © 2024 Elsevier B.V.